Glucosinolate-Enriched Fractions from Maca (Lepidium meyenii) Exert Myrosinase-Dependent Cytotoxic Effects against HepG2/C3A and HT29 Tumor Cell Lines - Lenzi, Raquely M.; Campestrini, Luciano Henrique; Semprebon, Simone Cristine; Paschoal, J. A.R.; Silva, Monique A.G.; Zawadzki-Baggio, Selma Faria; Mantovani, Mário Sérgio; Petkowicz, Carmen L.O.; Maurer, Juliana Bello Baron (Nutrition and Cancer, 2021)
The consumption of glucosinolate (GL)-rich foods, including Brassica vegetables, such as mustard, broccoli, and maca, is associated with decreased risk of developing cancer. The GL content in maca, which is recognized as a “superfood”, is approximately 100-times higher than that in other brassicas. Although maca is a potential dietary source of GLs, limited studies have examined the bioactivity of maca GLs using the combination of chemical characterization and bioassays. In this study, the fractions (Lm-II and Lm-III) rich in intact GLs (glucotropaeolin and glucolimnanthin) were isolated and characterized from maca ethanolic extracts using chromatography and mass spectrometry. Additionally, the growth-inhibitory effects of Lm-II and Lm-II fractions against hepatocellular carcinoma (HepG2/C3A) and colon adenocarcinoma (HT29) cell lines were examined in the absence or presence of myrosinase (MYR). Fractions lacking low molecular weight sugars dose-dependently exerted cytotoxic effects in the presence of MYR. The half-maximal inhibitory concentration values of Lm-II and Lm-III against HepG2/C3A were 118.8 and 69.9 µg/mL, respectively, while those against HT29 were 102.6 and 71.5 µg/mL, respectively. These results suggest that the anticancer properties of maca can be attributed to GLs and corroborate the categorization of maca as a “superfood.” Supplemental data for this article is available online at https://doi.org/10.1080/01635581.2021.1952444. © 2021 Taylor & Francis Group, LLC.